Aesthetic and World Politics by Roland Bleiker. Basingtoke, Hampshire: Palgrave Macmillan, 2009. Hardcover: 271 pp. - Siti Aliyuna Pratisti; Junita Budi Rachman (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2017)
Aesthetic approach to politics is not really something considered as a novelty. Immanuel Kant has described the aesthetic relationship with rationality way back in the 17th century, as well as Friedrich Nietzsche and Jaques Rancier as a more contemporary counterpart. In the field of international relations, the study of aesthetics has been raised by a number of reviewers – from James Der Derian, Costas Constantinou, David Campbell, to Anthony Burke – who began to lay aesthetics as a foothold in approaching various phenomena. Roland Bleiker is one of the most consistent among them. In an essay entitled